Anatomico-radiological Study of the Bifurcate Ligament of the Foot with Clinical Significance - Kafka, Rene M (Cureus, 2019)
Introduction Lateral ankle sprain caused by forcible plantar flexion and inversion of the foot commonly damages the anterior talofibular ligament and other ligaments. Unfortunately, involvement of the bifurcate ligament (BL) is often overlooked when assessing such injuries in clinical practice and identification of this ligament on magnetic resonance (MR) scans can be challenging. Anatomically, the BL is a Y-shaped structure with two bands: the calcaneonavicular ligament (CNL) and calcaneocuboid ligament (CCL). There are few anatomical studies on the morphometric characteristics of the BL and even fewer biomechanical studies. Therefore, the objective of this anatomico-radiological study was to investigate the morphology of the BL using a multifaceted approach, and classify the fiber characteristics of the CNL and CCL. Materials and methods We measured the length and the width of 53 embalmed cadaveric feet. Meticulous dissection of each foot was performed to expose the BL. Measurements of the length, width, thickness, and shape of the CNL and CCL were taken using a digital caliper. We also documented the fiber orientation of each ligament, and used a goniometer to measure the bifurcation angle between the CNL and CCL via two methods. Confirmatory histologic analysis of the ligaments was performed and digital radiographs of the ligaments with attached radiopaque monofilament were taken. We also included an MR scan of the BL. Using descriptive and inferential statistics, we documented any significant relationships between the variables. Results  Mean (range) age at death of cadavers was 76 (42-94) years. The CNL was found in all the feet and the CCL was not present in 9.4% of the feet. Mean (standard deviation) length of the CNL and CCL was 22.7 (4.12) mm and 10.9 (2.53) mm, respectively. Mean (standard deviation) thickness of the CNL and CCL was 3.23 (1.56) mm and 1.48 (0.71) mm, respectively. Related to ligament morphology, the CNL was most frequently cord shaped (67.92%) and the CCL was most frequently flat shaped (83.33%). The mean bifurcation angle measured 32.75(o )and 29.31(o )in methods 1 and 2, respectively. The correlation between the two measured angles was very strong (p < 0.001). Discussion We found that 90.6% of feet had both the CNL and CCL, 9.4% had the CNL and no CCL, and none (0%) had the CCL and no CNL. These frequencies are similar to a recent Japanese study. Our sample of donors were American and predominantly white. Whether the difference in frequencies between the studies is related to ethnicity is unknown and requires future investigation. Interestingly, on average the CNLs were twice as long and twice as thick as the CCLs. The CCLs tended to be wider distally and tapered compared to the CNLs. Conclusions Our findings better classify the morphology and fiber orientation of the BL. Coupled with the radiographs and MR scan, our data may be of particular value to radiologists and surgeons. Our BL fiber orientation classification system and angle measurements can pave the way for future biomechanical studies to investigate any relationships between fiber type, angle, and strength of the constituent bands. More accurate descriptions of the BL should lead to improved diagnosis and treatment of ligamentous injuries of the foot.